Minimizing unnecessary brain magnetic resonance imaging in pediatric endocrinology: a retrospective cohort analysis - Marin, Maura; Murru, Flora Maria; Baldo, Francesco; Tamaro, Gianluca; Faleschini, Elena; Barbi, Egidio; Tornese, Gianluca (Frontiers in Endocrinology, 2024)
Background: Brain magnetic resonance imaging (MRI) is mandatory or highly recommended in many pediatric endocrinological conditions to detect causative anatomic anomalies and rule out neoplastic lesions. However, MRI can also show findings associated with the underlying clinical condition, as well as unrelated "incidentalomas". These latter findings are often abnormalities with a high incidence in the general population for which there is no clear literature regarding their management, especially in pediatric patients. The present study aimed to evaluate the number of unnecessary performed MRIs in pediatric endocrinology.Methods: Retrospective analysis on 584 MRI scans performed in 414 patients (254 growth hormone deficiency, 41 other causes of short stature, 116 central precocious puberty).The MRI scans were completely normal in 67% of the individuals, and the prevalence of individuals who underwent more than one MRI was 18%, with no significant differences among the groups. The overall prevalence of incidentalomas was 17%. Among 170 repeated MRI scans, 147 (86%) were not required according to a dedicated protocol. Only five patients (4 GHD, 1 Noonan) correctly repeated the MRI. All the repeated MRI scans did not reveal any progression in the findings. If we include the MRIs performed in cases of OCSS other than Noonan syndrome (n=32) and girls with CPP older than 6 years (n=89), an additional 121 MRIs could have been avoided, leading to a total number of unnecessary MRIs to 268 (46%).Conclusions: Only a few specific neuroimaging findings in endocrinologic pediatric patients warrant further investigation, while too often repeated imaging is carried out unnecessarily. We advocate the importance of guidelines to reduce costs for both the healthcare system and patients' families, as well as to alleviate physical and psychological distress for patients and caregivers.